2007
DOI: 10.1007/s10620-006-9142-0
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of ERCP in the Management of Duct-to-Duct Anastomotic Strictures in Orthotopic Liver Transplant

Abstract: This study sought to determine the efficacy of endoscopic treatment of duct-to-duct anastomotic stricture in orthotopic liver transplant. A retrospective chart and database review was carried out using procedure and diagnosis codes during the period of 1997-2001. One hundred ninety-eight adult patients underwent orthotopic liver transplantation from 1997 to 2001. Fifteen patients (age 52+/-9 years; 60% women) with duct-to-duct anastomotic strictures were identified. They underwent a total of 53 endoscopic retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…These results are in line with another published report [23]. However, in contrast several other authors reported a shorter [24] or longer [4,5,9,25] time period from liver transplantation to the development of biliary stricture. Similar to our series, Graziadei et al [4] distinguished between anastomotic and non-anastomotic strictures after liver transplantation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in line with another published report [23]. However, in contrast several other authors reported a shorter [24] or longer [4,5,9,25] time period from liver transplantation to the development of biliary stricture. Similar to our series, Graziadei et al [4] distinguished between anastomotic and non-anastomotic strictures after liver transplantation.…”
Section: Discussionsupporting
confidence: 92%
“…The median duration of successful therapy was respectively 9, 11 and 10 months. Several other authors also reported successful endoscopic and/or percutaneous transhepatic therapy in most patients with biliary stricture after liver transplantation [4,12,[23][24][25]. Holt et al [12] observed in a prospective study design 791 adults who underwent liver transplantation; 53 out of 791 patients were diagnosed with biliary anastomotic stricture.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on this treatment, with some authors supporting alternative timing while others preferring single stents or dilation alone to minimize complications . However, this strategy requires repeated hospital admissions and endoscopic procedures and exposes patients to ERCP‐associated morbidity . Kobayashi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the number of plastic stents (PS) will progressively dilate a stricture of the common bile duct (CBD) or major papilla . Placement of MPS has been revealed to be effective in managing BBS with stricture resolution rates ranging from 78% to 85% . Main drawbacks are need for frequent stent exchange, either scheduled tri‐monthly or unscheduled after stent occlusion, and relative technical challenge in inserting multiple stents side‐by‐side across the stricture …”
Section: Introductionmentioning
confidence: 99%